2010
DOI: 10.1103/physrevlett.104.225001
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of an XUV Photogenerated Solid-Density Aluminum Plasma

Abstract: By use of high intensity XUV radiation from the FLASH free-electron laser at DESY, we have created highly excited exotic states of matter in solid-density aluminum samples. The XUV intensity is sufficiently high to excite an inner-shell electron from a large fraction of the atoms in the focal region. We show that soft-x-ray emission spectroscopy measurements reveal the electronic temperature and density of this highly excited system immediately after the excitation pulse, with detailed calculations of the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 32 publications
4
56
0
Order By: Relevance
“…It enables creating and probing plasmas, 14,15 hot dense matter, [15][16][17] and warm dense matter, 18,19 as well as the investigation of the interaction of low-fluence ultrafast laser pulses with matter, with applications to structural studies within solidstate physics, 11,[20][21][22][23] nanophysics, 24 molecular physics, and biophysics. 25 The presently operating free-electron lasers can produce laser pulses with durations of a few tens down to a few femtoseconds.…”
Section: Introductionmentioning
confidence: 99%
“…It enables creating and probing plasmas, 14,15 hot dense matter, [15][16][17] and warm dense matter, 18,19 as well as the investigation of the interaction of low-fluence ultrafast laser pulses with matter, with applications to structural studies within solidstate physics, 11,[20][21][22][23] nanophysics, 24 molecular physics, and biophysics. 25 The presently operating free-electron lasers can produce laser pulses with durations of a few tens down to a few femtoseconds.…”
Section: Introductionmentioning
confidence: 99%
“…The first years of research with short-wavelength FELs have demonstrated that at x-ray frequencies, laser-matter interactions are significantly different from interactions at * optical frequencies [10][11][12][13][14][15]. Understanding and controlling parameters that govern extreme interactions between x-ray radiation and materials are fundamentally important to many fields, including plasma acceleration and fusion research [16,17] and the structure determination of single biomolecules [18], viruses, or cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…The use of excited potentials in DFT calculations to study the electronic structure, often investigated experimentally by photoemission spectroscopy, is an established technique [22][23][24][25] , and has been recently adapted to the frozen-core PAW formalism to study the properties of dense plasmas 26 . This technique has since been successfully applied to interpret XANES measurements on dense Al plasmas with a 1s core hole 27 , and to the study of X-ray emission spectroscopy and electronic structure of L-shell-excited Al on the VUV FEL FLASH 28 .…”
mentioning
confidence: 99%